Genetic diversity of the sunflower caterpillar (Chlosyne lacinia saundersii Doubleday and Hewitson) (Lepidoptera: Nymphalidae) populations determined by molecular RAPD markers - Fabiane Cunha (Anais da Academia Brasileira de Ciências, 2010)
Chlosyne lacinia saundersii is one of the most important pests of sunflower and it is the main target of insecticides applications. Larvae were collected in Londrina (PR), Santa Maria (RS), Dourados (MS), Ribeirão Preto (SP), Brasília (DF), Barreiras (BA), Uberaba (MG) and Vilhena (RO). Genomic DNA was extracted and amplified with ten-mer primers, which produced 101 loci. The size of the RAPD amplicons ranged from 180 to 2564 bp. Polymorphism among populations ranged from 31% to 67%, with the highest polymorphisms of 57% and 67% being detected in Uberaba and Vilhena populations, respectively. Populations with the highest similarity determined with Dice coefficient were from Ribeirão Preto and Barreiras, while insects from Londrina showed the highest similarity among them. Gene flow of C. lacinia saundersii 1.1 was lower than those previously observed for the noctuid Anticarsia gemmatalis Hübner, suggesting that C. lacinia saundersii populations are more isolated than the ones of this noctuid. Through the Analysis of Molecular Variance (AMOVA), RAPD variance was 33.64% among geographical populations and 66.36% within populations. These results suggest that populations of C. lacinia saundersii are genetically structured.